PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Evi Mutia; Zuraida Zuraida; Devi Andriani (Program Magister Akuntansi Unsyiah, 2011)
This study aims to examine and analyses about the effect of company size, profitability and size of board of commissioner on the corporate social responsibility disclosure. The type of data used are secondary data, the data used are the annual report to manufacturing companies listed in Indonesia Stock Exchange (BEI) period 2006-2008. This study aims to examine and analyses about the effect, variables simultaneously test or the test individual effect of company size, profitability and size of board of commissioner on the corporate social responsibility disclosure.This research indicates that (1) company size, profitability and size of board of commissioner have a significant influence on the corporate social responsibility disclosure. (2) Company size have a significant influence on the corporate social responsibility disclosure.(3) Profitability have not a significant influence on the corporate social responsibility disclosure.(4)size of board of commissioner have a significant influence on the corporate social responsibility disclosure.Keywords: Company Size, Profitability, Size Of Board Of Commisioner and Corporate Social Responsibility Disclosure